2020
DOI: 10.3390/ma13081808
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Structural Characterization of Complex Oxide Eutectic Precursors from Polymer–Salt Xerogels Obtained by Microwave-Assisted Drying

Abstract: Sol–gel synthesis is an acknowledged method for obtaining fine inorganic powders of a different nature. Implementation of water-soluble polymers as gel-forming media makes this technique even more readily available, especially in cases where conventional gel formation is suppressed. In polymer–salt solutions, polymers serve as scaffolds for salt constituents’ bulk crystallization. When dried, solid salt particles are deposited on the polymer surface or in polymer matrix pores, which leads to higher grain size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Polymer drying is an important step in the majority of polymer processes since the engineered plastics are often hygroscopic; the presence of moisture (or other volatiles) can cause damages to the material as well as to the process devices. MW-assisted drying is a mature process that is now used at the industrial scale [111]; the effects of the electromagnetic MW field on the properties of polymers during the drying process are widely investigated and highlighted in recent reviews [112,113].…”
Section: Filler Polymer Matrix Improvements Observedmentioning
confidence: 99%
“…Polymer drying is an important step in the majority of polymer processes since the engineered plastics are often hygroscopic; the presence of moisture (or other volatiles) can cause damages to the material as well as to the process devices. MW-assisted drying is a mature process that is now used at the industrial scale [111]; the effects of the electromagnetic MW field on the properties of polymers during the drying process are widely investigated and highlighted in recent reviews [112,113].…”
Section: Filler Polymer Matrix Improvements Observedmentioning
confidence: 99%
“…Among the chemical methods in the liquid phase, the sol-gel technique is a versatile and efficient method for pure or doped metal oxide films or powders, as well as for oxide compounds preparation [21][22][23][24].…”
Section: General Consideration On the Sol-gel Chemistrymentioning
confidence: 99%
“…A group of researchers studied the deposition of mixed oxides CaO-Al 2 O 3 -Y 2 O 3 and MgO-Al 2 O 3 -Y 2 O 3 from salt-water-soluble polymer xerogels (PVP, polyvinyl alcohol, carbomethylcellulose) [13]. It was shown that, when dried using microwave radiation, the highest oxidation stability in xerogels was observed for those samples that included PVP.…”
Section: Introductionmentioning
confidence: 99%